The Management System Framework of Small- and Medium-Sized Enterprises Based on Strategic Flexible Management. (13th June 2022) - Zhao, Lihua; Wang, Jing; Li, Zhen
Abstract : The framework to learn how to manage SMEs is as simple as management. The first is to identify the internal control problems and causes of SMEs, and the reasons for the internal management problems of SMEs. Then, we analyzed the management system management and development of the business model industry-standard model. Based on the construction of industrial subsystems, a simple subsystem conversion system is developed, and a simple exchange strategy matrix for equipment measurement and decision-making is constructed. Finally, taking CW as an example, the company's case modeled and demonstrated the feasibility of the retrofit process, supporting the importance of the study. The experimental results show that asset specificity, organizational structure stability, cultural organization memory, and entrepreneur cognitive inertia are the main factors that promote the formation of strategic rigidity. Once the strategic rigidity is formed, it will have a negative effect on the enterprise, resulting in a lack of adaptability, lack of innovation power, and a decline in business performance, indicating the necessity and urgency of building an enterprise strategic flexibility system.